An Empirical Analysis of Imprisoning Drug Offenders - Ilyana Kuziemko
The number of prisoners incarcerated on drug-related offenses rose fifteen-fold between 1980 and 2000. This paper provides the first systematic empirical analysis of the implications of that dramatic shift in public policy. We show that the increase in drug prisoners led to reductions in expected time served for other crimes, especially for less serious offenses. Reductions in time served, however, increased other crimes by no more than a few percent. Moreover, incarcerating drug offenders is found to be almost as effective in reducing violent and property crime as locking up other types of offenders. We estimate that cocaine prices are 10-15 percent higher today as a consequence of increases in drug punishment since 1985. Based on previous estimates of the price elasticity of demand for cocaine, this implies a reduction in cocaine consumed of as much as 20 percent.